2013
DOI: 10.1007/s11481-012-9431-7
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Ameliorates the Neurodegenerative Pathology in A53T α-synuclein Cell Model of Parkinson’s Disease Through the Downregulation of mTOR/p70S6K Signaling and the Recovery of Macroautophagy

Abstract: Parkinson's disease (PD) is pathologically characterized by the presence of α-synuclein positive intracytoplasmic inclusions. The missense mutation, A53T α-synuclein is closely related to hereditary, early-onset PD. Accumulating evidences suggest that pathological accumulation of A53T α-synuclein protein will perturb itself to be efficiently and normally degraded through its usual degradation pathway, macroautophagy-lysosome pathway, therefore toxic effects on the neuron will be exacerbated. Based on the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(115 citation statements)
references
References 50 publications
2
111
1
1
Order By: Relevance
“…Since mTOR has been reported to be a client protein of Hsp90 (Moulick et al, 2011), we hypothesized that 19-Ph-GA might modulate mTOR activity in 5Y cells overexpressing A53T a-Syn. In contrast to a recent study (Jiang et al, 2013), we observed a sustained increase in the levels of LC3 II after overexpression of either A53T or WT a-Syn in 5Y cells, whereas the concomitant induction of phosphorylated mTOR (p-mTOR) and phosphorylated p70S6K (p-p70S6K) was only detected in A53T a-Syn-overexpressing cells (Fig. 7).…”
Section: Resultscontrasting
confidence: 99%
“…Since mTOR has been reported to be a client protein of Hsp90 (Moulick et al, 2011), we hypothesized that 19-Ph-GA might modulate mTOR activity in 5Y cells overexpressing A53T a-Syn. In contrast to a recent study (Jiang et al, 2013), we observed a sustained increase in the levels of LC3 II after overexpression of either A53T or WT a-Syn in 5Y cells, whereas the concomitant induction of phosphorylated mTOR (p-mTOR) and phosphorylated p70S6K (p-p70S6K) was only detected in A53T a-Syn-overexpressing cells (Fig. 7).…”
Section: Resultscontrasting
confidence: 99%
“…20 In contrast, SNCA A53T was shown to inhibit autophagy while WT SNCA had no obvious effect in a recent study. 26 However, the time-course changes in autophagy status had not been determined in these studies. To evaluate whether SNCA overexpression inhibits or activates autophagy, a range The levels of immunoprecipitated Becn1 were normalized to the corresponding levels of Becn1 in whole cell lysates.…”
Section: Discussionmentioning
confidence: 95%
“…These factors may contribute to the different outcomes of the previous studies. 20,26 Regardless of these factors, both WT and SNCA A53T inhibit autophagy at certain stages of overexpression. At different stages of SNCA pathology, the successive failure of protein degradation pathways (UPS, CMA, and autophagy) ultimately contributes to neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin regulates various growth factors, protein kinases, inflammatory cytokines and transcription factors to suppress the metastases and proliferation of human tumors (4). Other than anticancer and antitumor activities, it has also shown its effects against a variety of diseases such as respiratory tract infection, hepatic steatosis, skin photoageing, Parkinson's disease, pathogenesis of obesity, diabetes, HIV-associated diarrhea and Alzheimer's disease, through inhibition of amyloid beta oligomer formation (5)(6)(7)(8). The structure-activity relationship studies of curcumin molecule against different biological targets have indicated that the presence of two phenyl rings with a C-7 linker with ketoenol function (C=O groups as hydrogen acceptors and C-4 as a hydrogen donor) are most important for its biological activities.…”
mentioning
confidence: 99%